Urgensi Judgment Auditor dalam Otomatisasi Proses Audit - Padma Adriana Sari; Sumiadji Sumiadji; Atika Syuliswati (Organum: Jurnal Saintifik Manajemen dan Akuntansi, 2022)
Audit automation helps various stages in the audit process to provide convenience and speed in completing work, including the stages that are usually carried out using judgment. Currently, there have been several studies examining the use of information systems to replace the role of auditors in the audit process. Therefore, this study explores the impact of automation system on the auditor's judgment on the audit process. This study uses a qualitative descriptive method with in-depth interviews with senior auditors in public accounting firms. The results showed that the audit automation process has partially shifted the role of the judgment auditor, but there are still parts in the audit process that cannot be replaced by the system. Some judgments that are required by the auditor and cannot be replaced by the system are sample selections, fieldwork, and opinion determination. At these stages, the auditor needs flexibility to take actions that are in accordance with the audit conditions encountered and cannot be standardized in a standard carried out by the system. Auditors can focus on sharpening judgment skills in the sample selection process, fieldwork, and opinion determination so that it is expected to improve audit quality in the future.